Sensitivity of solar greenhouse envelopes to the thermal disfigurements and optimal selection of the thermal insulation quilt - Sun, Yachen; Zhang, Yao; Zhu, Chenmeng; Xu, Shaonan; Liu, Bowen; Cao, Yanfei; Zhou, Changji; Zhou, Yaqi; Zou, Zhirong; Bao, Encai (International Journal of Agricultural and Biological Engineering, 2021)
The objectives of the present work are focused on exploration of the reasons for temperature difference in different envelopes, the sensitivity of envelopes of solar greenhouse to thermal disfigurements and optimal selection of the thermal insulation quilt. Theoretical analysis and derivation are conducted according to the experimental results of surface temperature, convective heat transfer, and heat flux density in different envelopes which with thermal disfigurements of solar greenhouse using heat transfer theory. The results revealed that the difference of intrinsic thermal conductivity and thickness of the envelopes leads to difference in the thermal flux and thus in the surface temperature of different envelopes. Compared with the front roof and back roof, the wall is more sensitive to thermal disfigurements. According to the influence of thermal disfigurements on solar greenhouse temperature, the allowable thermal disfigurements area fraction of front roof and back roof are given. Based on the analysis of heat transfer theory and test results, the work given the expression of the thickness and thermal conductivity of thermal insulation quilt under different outdoor minimum temperatures for optimal selection of thermal insulation quilt based on comprehensive considering factors of the solar greenhouse structure, crop demand, outdoor minimum temperature, and insulation quilt properties. The results of this work gives technical criterion for whether the envelopes with thermal disfigurements needs to be repaired or replaced, and it also provide theoretical and technical support for design the solar greenhouse as well as methodological guidance for the optimal selection of the thermal insulation quilt.Keywords: solar greenhouse, thermal disfigurements, optimal selection, thermal insulation quiltDOI: 10.25165/j.ijabe.20211405.6311Citation: Sun Y C, Zhang Y, Zhu C M, Xu S N, Liu B W, Cao Y F, et al. Sensitivity of solar greenhouse envelopes to the thermal disfigurements and optimal selection of the thermal insulation quilt. Int J Agric & Biol Eng, 2021; 14(5): 50–55.